(untitled) (El-Wahat Journal for Research and Studies, 2026)
Edgar Allan Poe’s The Fall of the House of Usher (1839) has always fascinated audiences for its gothic qualities. Yet, Poe’s exploration of psychological issues such as madness, social anxiety and phobia makes his story as relevant in modern times as ever. Therefore, the present article proposes to study Edgar Allan Poe’s The Fall of the House of Usher in a modern context, highlighting the interplay between setting and mental condition. More accurately, it attempts to draw connections between madness in nineteenth century gothic fiction and psychological deterioration in the age of social media. It essentially aims to explore the effects of loneliness in the decayed house of Usher on Roderick’s and Madeline’s mental health and seeks to show how social media platforms contribute to a comparable sense of solitude. Moreover, it attempts to examine the drawbacks of loneliness on both Poe’s fictional characters and social media users. Findings showed that both in Poe’s work of fiction and in reality, extreme forms of solitude deeply affect physical health and psychological wellbeing, causing behavioral change which may culminate in depression. Most importantly, loneliness may eventually distort self-perception, resulting in self-alienation and identity loss. Therefore, it can be said that this research study contributes to understanding how nineteenth century literature serves as a lens through which to explore contemporary issues and challenges, particularly in the age of social media, providing foundations for future research on digital culture.